The Values of Maccera Tappareng Ceremony In Buginese Society at Wajo Regency (Local Culture Analysis) - Muhajir Muhajir (Tamaddun Life, 2018)
This paper discussed what values exist in the ceremony of Maccera Tappareng in Wajo Regency. This is intended to express all kinds of values in the ritual system of Maccera Tappareng, especially in Wajo Regency. This paper used the qualitative method with a descriptive approach and the data collection was done using triangulation are interviews, observation, and documents. The results of this study show the ceremony of Maccera Tappareng as local culture gives information about the values still exist in this culture in preserving the ceremony of Maccera Tappareng in Wajo regency.